ANALISIS PRAGMATIK DAN DIKSI PUISI “PADA SUATU PAGI HARI” KARYA SAPARDI DJOKO DAMONO - Yusliawati Yusliawati; Eka Nur Rachmawati; Mekar Ismayani (IKIP Siliwangi, 2019)
In this study based on curiosity to analyze the meaning contained in the sentence between sentences and diction contained in the poem